Dampak Gaya dan Peran Kepemimpinan Kiai dalam Penguatan Karakter Disiplin Santri - Nuraeni, Nuraeni; Sukandar, Ahmad; Helmawati, Helmawati (Edukasi: Journal of Educational Research, 2022)
The Kiai's leadership style and role is the most essential factor in determining policies and even strategies to address problematic issues. Therefore, a study of the impact of the style and role of Kiai leadership in Islamic boarding schools is very important to do, because the leadership of a Kiai will certainly have a major impact on the progress of Islamic boarding schools, especially in the formation and strengthening of students with character, discipline and high creativity in accordance with the educational goals of the Islamic boarding school. boarding school. In the Qur'an, it is revealed that Allah created humans on this earth, one of which is a leader who is able to regulate and maintain nature properly and does not cause damage. Judging from the leadership criteria, rationalism and humanism leadership are more suitable to be applied by leaders. Leadership is the process of influencing a person/group in activities to achieve certain goals. This study aims to analyze the impact of the Kiai's leadership style and role in strengthening the disciplined character of students at Al Jumhuriyah Islamic Boarding School Subang. The approach used in this research is qualitative research with the type of research being case studies. The data analysis in this research is in the form of descriptive data analysis techniques, namely the analysis method in the form of words. The results found in the field in this study are the impact of the Kiai's leadership style and role in strengthening the disciplined character of students at Al Jumhuriyah Islamic Boarding School Subang which has been seen in changes in the personality of students in actions and speech. These changes arise from the style and role of the Kiai in leading. The Kiai's democratic and charismatic leadership style and the Kiai's role as caregivers, role models for parents, leaders, motivators provide strengthening of the character of students in tolerance of groups, simple life, honesty, patience, sincerity, independence and confidence in changing for the better. Barriers in strengthening the character of students are influenced by internal and external factors. The solution to these obstacles can be overcome by applying the method of character education, namely habituation, exemplary and management of pesantren education. Therefore, in leading a pesantren, a Kiai should have a style and role in carrying out his leadership, so that it will have a positive impact on the disciplined character of the santri, and that has been done by Kiai Deden Al Jamhuri, S. H. I in strengthening the disciplinary character of the santri at the Modern Al Islamic Boarding School Jumhuriyah.